THE EFFECTIVENESS OF DIGITAL ADS AND E-COMMERCE PLATFORMS ON REACHING TARGET AUDIENCE - M G, Dr. Lakshmipathaiah (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the effectiveness of digital ads and e-commerce platforms in reaching target audiences, with a focus on key performance metrics. Utilizing a descriptive research methodology and a sample of 200 respondents from various megastores in Mysuru City, the research employed ANOVA and homogeneity tests to analyze data collected through structured questionnaires. Findings reveal that Perceived Value and User Experience significantly influence Ad Effectiveness, while factors like Consumer Engagement and Brand Awareness show limited impact. The study emphasizes the need for enhanced value propositions and improved user interfaces in digital ads. Recommendations include optimizing ad recall strategies and refining content to better engage the target audience. These insights offer valuable guidance for marketers aiming to enhance digital advertising efficacy and e-commerce performance.